Psychologically informed physical fitness practice in schools: A field experiment. (January 2019) - Vazou, Spyridoula; Mischo, Amanda; Ladwig, Matthew A.; Ekkekakis, Panteleimon; Welk, Gregory
Abstract: Objectives: Physical education could play a role in attenuating the decline in physical activity during the childhood-to-adolescence transition and inspiring children to adopt a lifelong physical activity habit. While psychological theories (e.g., Self-Determination Theory, Achievement Goal Theory) offer pointers for desirable changes to practice norms, experimental tests of the effectiveness of theory-based interventions in school settings are lacking. In this study, we compared the effects of a "traditional" and a "novel" physical education lesson on affective valence, enjoyment, and perceived satisfaction of the psychological needs for autonomy, competence, and relatedness. Design: Within-subjects field experiment, with two counterbalanced conditions. Method: The participants were 148 children (4-6th grade, 52% female). Both lessons consisted of practicing aerobic capacity (running), core (curl-ups), and upper-body (push-ups) strength and endurance. In the "traditional" lesson, practice procedures followed FITNESSGRAM™ test instructions. The "novel" lesson incorporated elements designed to address basic psychological needs (e.g., freedom to select preferred running path, positive interactions among peers) and other evidence-supported modifications (e.g., music and video). Results: Affective valence declined in the "traditional" lesson but remained stable in the "novel" lesson. Enjoyment and need-satisfaction for competence were higher after the "novel" lesson. These differences occurred despite no significant differences in total accelerometer-assessed moderate-to-vigorous physical activity and the intensity of the aerobic components. Conclusions: Easily implementable, theory-based modifications to physical education practices could improve the experiences derived by students. In turn, experiencing physical education as more pleasant, enjoyable, and need-supportive could raise the odds of long-term physical activity participation. Highlights: Easy, theory-based changes to physical education can improve students' experiences. Fitness practice can be pleasant, enjoyable, and need-supportive. Vigorous intensity exercise can feel good with structural changes in physical education.